2015
DOI: 10.1371/journal.pone.0123645
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity Impacts on Epstein-Barr Virus Infection of AGS Cells

Abstract: The Epstein-Barr virus (EBV) is transmitted from host-to-host via saliva and is associated with epithelial malignancies including nasopharyngeal carcinoma (NPC) and some forms of gastric carcinoma (GC). Nevertheless, EBV does not transform epithelial cells in vitro where it is rapidly lost from infected primary epithelial cells or epithelial tumor cells. Long-term infection by EBV, however, can be established in hTERT-immortalized nasopharyngeal epithelial cells. Here, we hypothesized that increased telomerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Previously we and others showed that the molecular diversity of EBV‐reactive IgG and IgA responses varies greatly among NPC patients, reflecting heterogeneous EBV antigen exposure during NPC development . We suggest that VCA‐IgA reactivity reflects loco‐regional virus replication events outside the initiating tumor mass, potentially contributing to tumor initiation by providing infectious EBV to infect susceptible cells capable of maintaining the viral genome, as recently identified . Recently, the combination of EBV IgA serology with EBV‐DNA load analysis in NP brushings has been proposed as preferred method for population screening programs to identify early stage NPC …”
Section: Discussionsupporting
confidence: 51%
“…Previously we and others showed that the molecular diversity of EBV‐reactive IgG and IgA responses varies greatly among NPC patients, reflecting heterogeneous EBV antigen exposure during NPC development . We suggest that VCA‐IgA reactivity reflects loco‐regional virus replication events outside the initiating tumor mass, potentially contributing to tumor initiation by providing infectious EBV to infect susceptible cells capable of maintaining the viral genome, as recently identified . Recently, the combination of EBV IgA serology with EBV‐DNA load analysis in NP brushings has been proposed as preferred method for population screening programs to identify early stage NPC …”
Section: Discussionsupporting
confidence: 51%
“…This cell line was derived from fragments of a tumor resected from a 54-year-old female patient who had received no prior therapy in 1979 (13). As a common GC cell line, AGS has been used widely in GC-related studies (14)(15)(16). The expression of AFP in AGS was reported by Chen et al in 2003 (17); however, the biological functions of AFP in AGS, particularly in invasion and metastasis remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the impact of TERT on EBV infection and viral gene expression has also been studied in epithelial cells [ 49 ]. Gastric carcinoma AGS cells with high telomerase activity show increased expression of latent EBV genes, indicating that telomerase directly contributes toward favoring the latency program in epithelial EBV-infected cells [ 49 ]. Thus, the ability of TERT to favor the latency program in both B lymphocytes and epithelial EBV-infected cells further supports the crucial role of telomerase in EBV-driven malignancies.…”
Section: Introductionmentioning
confidence: 99%